Methodological approaches to assessing economic security in foreign trade - Zverev, Alexey; Kuznetsova, Olga; Mishina, Maria; Rebrina, Tatiana; Aleshin, Evgeny (Amazonia Investiga, 2023)
Economic security of foreign trade can be measured through a set of different special indicators with no standardised composition and regulations. The purpose of the study is to analyse the existing methods for assessing the level of economic security in the sphere of foreign trade and to develop an optimal system of indicators for its identification. The research involved scientific publications by national and foreign scholars, official statistical data in the field of Russian export and import as well as the following methods – monography, observation, comparison, economic analysis, analogue and hypothetical modelling. The article assesses various indicators for assessing economic security in foreign trade, applied in Russia and abroad. The authors identified the most informative indicators, proposed a number of threshold requirements for them; included two additional indicators (increment rate of counterfeit goods, share of counterfeit goods in imports), developed a rating-based approach to identify high, average, low, critical and catastrophic levels of economic security in the sphere of export/import operations. Foreign trade is an important activity for any state; however, it involves a number of risks and threats to be carefully assessed and minimised. Therefore, it is necessary to select efficient ways of assessing economic security in foreign trade transactions.